Efforts to Improve Islamic Education Learning Outcomes Through the Use of the Demonstration Method of Funeral Prayer Materials at Lam Awee State Elementary School - Nurhayati; Junaida (MANDAILING GLOBAL EDUKASIA, 2024)
Efforts to Improve Learning Outcomes in Islamic Religious Education Through the Use of Funeral Prayer Material Demonstration Method for Class VI Semester I Students at Lam Awee State Elementary School in the 2022/2023 Academic Year. This research aims to find out the improvement of student learning outcomes in Islamic Religious Education in particular Class VI by using the demonstration method on the funeral prayer material at SD Negeri Lam Awee in the 2022/2023 academic year. The type of this research is class action research (PTK) or action research. The subject of this research is a class VI student of Negeri Lam Awee SD. The results of this research show that there has been an increase. In cycle I, the results of student evaluations in the subject of Islamic Religious Education obtained an average value of 63.70, while in cycle II, an average value of 82.80 was obtained from the research. There was a significant and satisfactory increase and the level of completeness of students' learning in the learning process in cycle I was 40.00% and in cycle II was 100.00%. means there is an increase in student learning outcomes and the activity of the learning process of the students after conducting class action research. Thus, it can be concluded that there is a significant and satisfactory increase in learning outcomes after doing this research compared to before. And there was a change in the level of student activity that was quite high. So this research is considered successful.